2013
DOI: 10.1002/ejlt.201300087
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lipase production on crambe oil and meal by Fusarium sp. (Gibberella fujikuroi complex)

Abstract: This study provides a comparison of fermentation conditions for the production lipases by Fusarium sp. (Gibberella fujikuroi complex) isolate FCLA-MA-41 in submerged (SmF) and solid-state fermentation (SSF) using agro-industrial residues. To assess SmF, a univariate study of seven carbon sources (crambe, corn, linseed, olive, palm (dendê), soybean oils and chicken fat) and four nitrogen sources (ammonium sulfate, sodium nitrate, urea, yeast extract) was performed. The relationship among the concentrations of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…(GFC) FCLA-MA41 strain in SmF with culture medium containing crambe oil (17.5 mL/L), Triton X-100 (5 g/L), ammonium sulfate (5 g/L) and yeast extract (1 g/L) was proposed, resulting in a lipase titer of 3.0 ± 0.25 U/mL (Oliveira et al, 2013). Although providethis provides lower activity than that obtained with chicken oil, the cost per unit of enzyme activity was also lower ($US 183.00 and $US 518.00/million Units of lipase with crambe oil and chicken fat, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(GFC) FCLA-MA41 strain in SmF with culture medium containing crambe oil (17.5 mL/L), Triton X-100 (5 g/L), ammonium sulfate (5 g/L) and yeast extract (1 g/L) was proposed, resulting in a lipase titer of 3.0 ± 0.25 U/mL (Oliveira et al, 2013). Although providethis provides lower activity than that obtained with chicken oil, the cost per unit of enzyme activity was also lower ($US 183.00 and $US 518.00/million Units of lipase with crambe oil and chicken fat, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…(Gibberella fujikuroi complex) FCLA-MA41 was isolated from decaying plant matter in the Atlantic Forest in the state of São Paulo (Brazil) and identified as described by Oliveira et al (2013). The fungal isolate was maintained on MEA medium (malt extract agar) and stored at 4°C.…”
Section: Microorganismmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipases also contribute to the development of a distinctive flavor during the ripening stage of food production, which acts on butterfat to produce the characteristic flavors of several cheese types (Binod et al, 2013). (Oliveira et al, 2013), and P. chrysogenum, Trichoderma harzianum, and A. flavus (Toscano et al, 2013). (Oliveira et al, 2013), and P. chrysogenum, Trichoderma harzianum, and A. flavus (Toscano et al, 2013).…”
Section: Production Of Microbial Enzymes For Food Applicationsmentioning
confidence: 98%
“…Oil seed cake (Venkatesagowda et al, 2014), rice bran, wheat bran, canola seed oil cake, sunflower hulls, peanut shells (Amin and Bhatti, 2014), pumpkin seed flour (Zubiolo et al, 2014), jatropha seed cake (Veerabhadrappa et al, 2014), crambe oil, corn oil, linseed oil, olive oil, palm oil, soybean oil, chicken fat (Oliveira et al, 2013), mustard oil cake (Imandi et al, 2013), sesame oil cake, groundnut oil cake, coconut oil cake (Rajendran and Thangavelu, 2013), and fish waste meal (Esakkiraj et al, 2012) have been reported as raw materials and carbon sources for microbial lipase production in the past few years.…”
Section: Production Of Microbial Enzymes For Food Applicationsmentioning
confidence: 99%